A SCOPING REVIEW OF UNDERSTANDING HOW SOCIAL MEDIA NARRATIVES SHAPE TRAVEL DECISIONS OF MALAYSIAN YOUTH : A SCOPING REVIEW OF QUALITATIVE STUDIES - Siti Yuliandi, Ahmad; Nurshafina, Mohd Yusoff (Korint Yayincilik, 2025)
In Malaysia's rapidly digitalising tourism landscape, social media platforms such as TikTok, Instagram, and YouTube have become central to how youth discover, imagine, and select travel destinations. While past studies confirm that social media strongly influences youth travel motivation, most have focused on general motivation rather than exploring how Malaysian youth interpret and internalise travel narratives, or how platform design subtly shapes destination appeal. The study aims to explore how symbolic, emotional, and technological factors intersect in youth travel decision-making, moving beyond functional motivations to highlight narrative and identity-driven processes. This study addresses these gaps by adopting a qualitative narrative inquiry approach to understand how Malaysian youth aged 18–30 construct meaning from social media stories when planning travel. Data were collected through semi-structured online interviews with purposely selected youth who actively engage with travel content on social media. Sampling continued until thematic saturation was achieved, ensuring a diverse yet relevant representation of perspectives. Thematic analysis was used, following a systematic six-phase process, to identify key patterns related to research objectives. The findings aim to provide deeper theoretical insights for academic researchers and practical implications for tourism marketers, travel agencies, and content creators, enabling them to design campaigns and content that authentically resonate with Malaysian youth. By revealing how digital stories are internalised, this research contributes to a richer understanding of the evolving relationship between social media narratives and youth travel choices